2004
DOI: 10.1002/ijc.20607
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of Protease activated receptor 1 (Par1) and pY397FAK in benign and malignant human ovarian tissue samples

Abstract: Protease activated receptors (PAR) form a family of G-protein coupled receptors (GPCR) encoding their own ligands and uniquely activated via proteolytic cleavage. Although proteases in general have been implicated in the remodeling of the extracellular tumor microenvironment, the role of cell surface receptors activated by proteolysis is now emerging. In our present study we investigated the expression pattern of protease activated receptor 1 hPar1 in ovarian carcinoma tissue samples. Abundant hPar1 mRNA and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 37 publications
4
76
0
1
Order By: Relevance
“…FAK also becomes autophosphorylated at Tyr 397 through binding with β1 integrins in endothelial cells in response to shear stress (24) and in breast adenocarcinoma cells when exposed to 3 μm/s IF as we have shown previously (17). Furthermore, phosphorylation of FAK at Tyr 397 is required for invadopodia formation for breast cancer cells (25), and FAK PY397 is differentially expressed in metastatic cervical carcinoma relative to noncancerous epithelium (26). FAK is required for mechanical stress-induced cell polarization (6,27), and the FAK-paxillin-vinculin signaling complex is required for rigidity sensing and durotaxis (9).…”
Section: Significancesupporting
confidence: 54%
“…FAK also becomes autophosphorylated at Tyr 397 through binding with β1 integrins in endothelial cells in response to shear stress (24) and in breast adenocarcinoma cells when exposed to 3 μm/s IF as we have shown previously (17). Furthermore, phosphorylation of FAK at Tyr 397 is required for invadopodia formation for breast cancer cells (25), and FAK PY397 is differentially expressed in metastatic cervical carcinoma relative to noncancerous epithelium (26). FAK is required for mechanical stress-induced cell polarization (6,27), and the FAK-paxillin-vinculin signaling complex is required for rigidity sensing and durotaxis (9).…”
Section: Significancesupporting
confidence: 54%
“…FAK plays a critical role in the regulation of cancer initiation, progression, and metastasis, and its aberrantly high expression and phosphorylation are directly correlated with the malignancy of a variety of human cancers (3,4,6,7,(11)(12)(13)(14). FAK expression or activity is barely detectable in normal human ovarian epithelium but highly elevated in ϳ70% of human ovarian tumors and is associated with high risk clinical features and poor patient survival (4,7).…”
Section: Discussionmentioning
confidence: 99%
“…FAK expression or activity is barely detectable in normal human ovarian epithelium but highly elevated in ϳ70% of human ovarian tumors and is associated with high risk clinical features and poor patient survival (4,7). In addition to SKOV3ip1, our recent studies have demonstrated that KLF8 is also highly overexpressed in several other human ovarian cancer cell lines and primary ovarian tumor tissues (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, numerous studies have shown that PAR1 is overexpressed in invasive and metastatic tumors and that its expression levels directly correlate with the degree of invasiveness of the cancer [20][21][22][23][24][25][26][27][28]. Based on these facts, this receptor is starting to be also considered a promising target for cancer therapy [15], particularly in the search of angiogenesis inhibitors [29].…”
Section: Introductionmentioning
confidence: 99%